Studi Deskriptif Pengetahuan Diare Akibat Jajanan Siswa SMKN 01 Pemalang - Pratama, Andhika Gilang (Politeknik Kementerian Kesehatan Banjarmasin, 2025)
This study aimed to determine the knowledge level of students at SMKN 01 Pemalang regarding the risk of diarrhea caused by consuming street food. This was a descriptive quantitative study with a cross-sectional design. A total of 269 respondents were selected using total sampling technique. Data were collected via a validated online questionnaire. Results showed that the majority of respondents had good knowledge (90.3%), while only 9.7% had poor knowledge. The conclusion of this study is that students generally understand the risks of consuming unhygienic food, yet educational interventions are still needed to raise awareness and reinforce clean and healthy living behavior.